Argumentum Ad Hominem Mantık Yanılgısı - Durhan, Gülümser (Muş Alparslan Üniversitesi, 2021)
Ad hominem arguments are very common in political debates, legal disputes, and everyday speech. The reason why this is treated as a logical error is that the argument put forward by a person is clearly often irrelevant to the character, circumstances, situation or behavior of the opponent. So that an ad hominem argument is an argument about the credibility of a person in performing a certain function that makes an attack on the basis of certain attributes related to that person. Based on this definition, the purpose of this study is to make a general description of ad hominem arguments based on some of the false types of ad hominem arguments and to illustrate these various types of fallacy with examples from daily life. In addition, this study is a search for an answer to the question of whether these fallacy are always misleading and a solution to the problem of whether they are really logical fallacy.

Ad hominem argümanları, politik tartışmalarda, hukuki münakaşalarda ve günlük konuşmalarda oldukça yaygın bir şekilde yer almaktadır. Bunun bir mantık yanılgısı olarak ele alınmasının nedeni ise, bir kişinin ileri sürdüğü argümanın, açık bir şekilde, karşı tarafın karakteri, içinde bulunduğu koşulları, durumu veya davranışlarıyla çoğu kez alakasız olmasıdır. Öyle ki bir ad hominem argümanı, bir kişinin belirli bir işlevi yerine getirmesindeki güvenilirliği hakkında, söz konusu kişiyle ilgili bazı niteliklere dayanarak bir saldırıda bulunan argümandır. Bu tanıma dayanarak, amacımız, ad hominem argümanlarının yanlış olan bazı türleri üzerinden genel bir tanımlamasını yapmak ve bu çeşitli yanlışlık türlerini, günlük yaşamdan örneklerle serimlemektir. Ayrıca bu çalışma, bu yanılgıların her zaman yanıltıcı olup olmadığı sorusuna cevap bulmak ve gerçekten bunların mantık yanılgısı mı olduğu sorununa çözüm arayışıdır.
Argumentum Ad Hominem Logic Fallacy
anemon
Keywords: Logic; Ad hominem; Sophistry; Fallacy; Mantık; Ad hominem; safsata; yanlış